ARTIFICIAL INTELLIGENCE IN SCHOOL SECURITY: OPPORTUNITY AND CHALLENGES (UNIZIK Journal of Educational Management and Policy, 2026)
This study investigates artificial intelligence in school security: opportunity and challenges.Drawing insights from a comprehensive review of existing literature and framed within thecontext of Self-determination Theory (SDT), the research explores the multifaceted contributionsof AI across various stages of curriculum development and execution. The study reveals that AItechnologies, including machine learning and natural language processing, play a pivotal role inenhancing educational practices. Notably, AI facilitates personalized learning experiences,automates assessments, and optimizes curriculum design by analyzing extensive datasets onstudent performance. The findings underscore the potential of AI to address scalability issues ineducation, offering a dynamic approach to curriculum development that considers individuallearner needs and ensures the delivery of high-quality educational content. Moreover, the studyidentifies future prospects for AI in education, envisioning advancements in adaptive learningsystems, intelligent tutoring, and expanded applications of AI-driven virtual assistants. Despitethe positive impacts, the research acknowledges challenges, such as ethical concerns and theimperative for workforce re-skilling.
Keywords: Artificial intelligence, School, Security, Opportunities, Challenges, Education